2020
DOI: 10.1111/ijsw.12429
|View full text |Cite
|
Sign up to set email alerts
|

Building racial bridges? Social capital among community gardeners in US food deserts

Abstract: This study examined the relationship between race and racial diversity on social capital in community gardens located in food deserts in the southeastern region of the USA. Using snowball methods, a sample of 52 gardeners who represented 10 community gardens was obtained. Cross‐level regression models were performed using two different aspects of social capital: one’s “sense of community” and the “number of resources” a gardener could obtain from fellow gardeners, as dependent variables. Results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This is consistent with the findings of a large range of research into gardening which shows a similar disproportion of gender, with groups typically having older, female participants ( Shiue, 2016 ; Liamputtong and Sanchez, 2018 ; Kingsley et al, 2019 ; Robbins and Seibel, 2020 ). The group also appears to lack ethnic diversity; an issue shared by several previous community gardening studies ( Glover, 2004 ; Firth et al, 2011 ; Jettner and Secret, 2020 ). Some describe the occurrence of this ‘ethnic homogeneity’ in gardening as a natural phenomenon that perceived racial differences are avoided because they would negatively impact the members’ sense of community ( Jettner and Secret, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This is consistent with the findings of a large range of research into gardening which shows a similar disproportion of gender, with groups typically having older, female participants ( Shiue, 2016 ; Liamputtong and Sanchez, 2018 ; Kingsley et al, 2019 ; Robbins and Seibel, 2020 ). The group also appears to lack ethnic diversity; an issue shared by several previous community gardening studies ( Glover, 2004 ; Firth et al, 2011 ; Jettner and Secret, 2020 ). Some describe the occurrence of this ‘ethnic homogeneity’ in gardening as a natural phenomenon that perceived racial differences are avoided because they would negatively impact the members’ sense of community ( Jettner and Secret, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…The group also appears to lack ethnic diversity; an issue shared by several previous community gardening studies ( Glover, 2004 ; Firth et al, 2011 ; Jettner and Secret, 2020 ). Some describe the occurrence of this ‘ethnic homogeneity’ in gardening as a natural phenomenon that perceived racial differences are avoided because they would negatively impact the members’ sense of community ( Jettner and Secret, 2020 ). It is suggested that some gardening groups primarily attract white, middle-class gardeners as participants, but understanding why this is still ongoing is a featured recommendation of previous research ( Firth et al, 2011 ; Jettner and Secret, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The built environments become nonfunctional due to incompetent management, the end of the shelf life, lack of budget for maintenance, and disregard for the quality of life [12]. Recently, neighborhood social capital in urban plans has focused on two aspects: First, community service and local management, including public health, community governance, disaster relief, protecting vulnerable groups, and other social adjustment mechanisms [13][14][15][16][17][18]. Second, it deals with the community space resources under the influence of the community material conditions; it mainly studies community facilities, the development of low-income neighborhoods, landscape greening, and increasing areas of housing and sports [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%